Microbiological monitoring of a multidisciplinary medical organization: the basis of strategic planning in the framework of the implementation of epidemiological safety - O. P. Bobrova; A. O. Fetisov; S. K. Zyryanov (Izdatelstvo OKI, 2024)
Relevance. Monitoring of antibiotic resistance and the frequency of isolation of microorganisms at the regional level in each medical organization is of paramount importance for the implementation of epidemiological safety. Objective.  To identify the main microbiological trends based on the analysis of the microflora of patients in a single - profile hospital in order to implement weaknesses in strategic planning activities.  Materials and methods. A comprehensive analysis of the pharmacoepidemiological results of the consumption of antimicrobial drugs with calculated drug resistance indices and microbiological monitoring data demonstrated the presence of weaknesses and strengths for the strategic development of a multidisciplinary hospital at the regional level in terms of epidemiological safety.  Results . Statistically significant differences in the microbiological structure of pathogens are predetermined by the profile of medical care. The main trends in the change in the microflora of a multidisciplinary hospital as a whole are the prevalence of fungal and gram-negative pathogens over gram-positive ones. The presence of a relatively high index of consumpion of cephalosporins of 3-4 generations, fluoroquinolones, carbapenems, protected penicillins determines the high drug resistance index of Klebsiella pneumoniae (0.86) and characterizes the main microbiological trends of a multidisciplinary clinic.  Conclusion. Risk stratification by the level of multidrug-resistant pathogens, the use of deterrent strategies for prescribing antimicrobials, the implementation of educational modules, the evaluation of the effectiveness and monitoring of the risk stratification program with in the framework of antimicrobial technologies, the analysis of microbial landscape data using decision support programs are the main tasks of the functioning of a multidisciplinary team of specialists in a multidisciplinary clinic to control antibiotic resistance.